Fine-grained pyrite in some Chinese coals. Issue 4 (July 2016) - Wang, Wenfeng; Sang, Shuxun; Bian, Zhengfu; Duan, Piaopiao; Qian, Fuchang; Lei, Shaogang; Qin, Yong
Fine-grained pyrite in some Chinese coals has been investigated, with analysis by optical microscopy and a scanning electron microscope equipped with energy dispersive X-ray spectrometer illustrating that the interaction between mineral and organic matters results in the irregular pyrite crystal present in coal. When considering the co-existing carbon, the density of fine-grained pyrite in coal is lower than that of mineral pyrite. Organic sulfur and pyritic sulfur in coal can be converted into each other under the favorable conditions. However, the fine-grained pyrite crystal pattern is still detected when the S/Fe ratio increases to 2:1, meaning that the fine-grained pyrite shifts from dissemination to crystallization. Fine-grained pyrite in coal has a strong activity and its surface is susceptible to be oxidized. Oxidized fine-grained pyrite usually forms sulfate (mainly gypsum), and sometimes may be converted to marcasite. Fine-grained pyrite in coal, when their granularity is small enough, may be chemically associated with organic components by non-pyritic Fe–S bond rather than physically embedded in coal matrix. So, it is not suitable to express the mineral using the FeS2 formula.